Penerapan Doktrin Fair Use Defense dan Prinsip Standar Minimum dalam Penyelesaian Sengketa Hak Cipta - Putu George Matthew Simbolon (CV. Social Politic Genius (SIGn), 2023)
This study aims to examine and analyze how disputes arising from copyright infringement can be resolved by applying the fair use defense doctrine in the copyright protection regime in Indonesia. This study uses normative legal research with the statute, conceptual, case, and comparative approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that Indonesia must apply the doctrine of fair use defense as a mechanism in copyright dispute settlement. Despite its unfamiliarity in Indonesia, the fair use defense aligns with the principle of minimum standards and the FET principle regulated in the TRIPs Agreement. This agreement binds Indonesia under Law Number 7 of 1994. The proportionality of this doctrine has also been tested through legal findings by the U.S. Supreme Court, which is based on Section 107 of the U.S. Copyright Act. Therefore, it is recommended that the House of Representatives amend Law Number 28 of 2014 to include more specific clauses explaining what factors qualify as fair use. In addition to amending Law Number 28 of 2014, it is recommended that the Government or the Supreme Court establish implementing regulations for Law Number 28 of 2014 concerning factors that qualify as fair use of copyrighted works. On the other hand, researchers and academics are encouraged to conduct further research on applying the fair use defense doctrine. This research can also provide valuable recommendations for the Government and the House of Representatives in strengthening Indonesia’s legal framework and copyright protection regime.